2015
DOI: 10.1371/journal.pone.0121505
|View full text |Cite|
|
Sign up to set email alerts
|

Expanding our Understanding of Sequence-Function Relationships of Type II Polyketide Biosynthetic Gene Clusters: Bioinformatics-Guided Identification of Frankiamicin A from Frankia sp. EAN1pec

Abstract: A large and rapidly increasing number of unstudied “orphan” natural product biosynthetic gene clusters are being uncovered in sequenced microbial genomes. An important goal of modern natural products research is to be able to accurately predict natural product structures and biosynthetic pathways from these gene cluster sequences. This requires both development of bioinformatic methods for global analysis of these gene clusters and experimental characterization of select products produced by gene clusters with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…4). We observe that the C19 KR was introduced into the ancestor of frankiamycin (32) and all other characterized clusters (ancestor 4).…”
Section: Resultsmentioning
confidence: 79%
“…4). We observe that the C19 KR was introduced into the ancestor of frankiamycin (32) and all other characterized clusters (ancestor 4).…”
Section: Resultsmentioning
confidence: 79%
“…Ogasawara et al . ( 86 ) developed Dynamite, a Python software package which uses a BLAST database to identify type I and type II PKS and NRPS gene clusters within the NCBI database, and conducted a global phylogenetic analysis of type II polyketide ketosynthases. However, at present, no software exists to predict the chemical structures of type II polyketides from genetic information.…”
Section: Methodsmentioning
confidence: 99%
“…Both the ketosynthase α (KSα) and chain length factor (CLF or KSβ) occupy distinct clades within ketosynthase phylogeny ( 87 ), and several studies ( 86 , 88 , 89 ) have reported that the length of the unreduced ketide chain produced by the minimal PKS can be reliably inferred from the primary sequence of the chain length factor. We therefore constructed new hidden Markov models for type II PKS KSα and CLF domains, and compiled a BLAST database of CLF domains annotated with the number of ketide chain extension cycles associated with the PKS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene prediction and annotation were carried out using RAST ( 14 ), incorporating the Glimmer ( 15 ) algorithm, and identified 10,999 putative protein-coding genes, 7 rRNAs, and 63 tRNAs. Twenty-two polyketide and nonribosomal peptide natural-product biosynthetic gene clusters, all of which were intact, including the error-free azicemicin cluster, were identified using Dynamite ( 16 ) and confirmed using antiSMASH ( 17 ).…”
Section: Genome Announcementmentioning
confidence: 99%